Persistence of drug therapy is associated with ischemic stroke and other vascular events in high-risk stroke population - Yi, Xingyang; Chen, Hong; Yu, Ming; Luo, Hua; Zhou, Ju; Wei, Wei; Wang, Yanfen; Chen, Xiaorong (Frontiers in Neurology, 2022)
The high risk stroke populations are significantly associated with an increased risk of stroke or other vascular events. Although proven stroke primary and secondary prevention medications are available, persistent use is required to be effective. However, medication compliance and its association with outcomes in the high risk stroke population have received limited study in China. Hence, according to the China National Stroke Screening Survey (CNSSS) programmeme in 2015, we performed this multi-center population based cross sectional survey and prospective cohort study in Sichuan of southwestern China. The residents aged ≥ 40 years volunteered to participate in face-to-face survey in 8 communities. Subjects with at least three of eight stroke related risk factors or a history of stroke were defined as high risk stroke population. The interviewers recorded individuals’ medications at face-to-face survey, and all the high risk stroke population was followed up for 4.7 years. The compliance of antihypertensives, hypoglycemics, lipid lowering medications, and antithrombotics for stroke was evaluated. The primary outcome was new stroke. Secondary outcomes included new composite vascular events of stroke, myocardial infarction and death during follow-up periods. Among 16892 participants, 2893 (17.1%) were high risk stroke population, 2698 (93.3%) completed to follow up. The 4.7-year compliance rate of antihypertensives, hypoglycemics, lipid lowering medications, and antithrombotics was 38.0%, 39.9%, 43.9%, and 59.8 %, respectively. During the 4.7-year follow-up, there were 118 (4.4%) new ischemic strokes, 24 (0.9%) hemorrhagic strokes, 53 (2.0%) myocardial infarctions, and 33(1.2%) deaths. After adjusting for the covariates, 4.7-year compliance of antihypertensives, hypoglycemics, lipid lowering therapy, and antithrombotics was independently associated with less new ischemic stroke and less new composite vascular events. Thus, more effective public education, efforts to understand and enhance compliance are crucial to improve population health, decrease stroke and other vascular events for the high risk stroke population.